CHARACTERISTICS OF PATIENTS WITH ACUTE APPENDICITIS AT RSUP DR. M. DJAMIL PADANG YEAR 2017-2019 - Desfina, Sherlia; Muhamad Ivan; Vina Tri Septiana; Primadella Fegita; Annisa Lidra Maribeth (Jurnal EduHealth, 2022)
Acute appendicitis is an abdominal emergency requiring immediate surgical intervention. Acute appendicitis is defined as acute inflammation of the appendix wall which is usually caused by obstruction of the appendix lumen. The development of an inflammatory process in acute appendicitis can result in perforation, abscess, illegality, peritonitis, or death if not managed properly. Objective: To determine the characteristics of acute appendicitis patients at DR. M. Djamil Padang in 2017 – 2019. Methods: The research design used was a categorical descriptive study with retrospective data collection methods. The population in this study were patients diagnosed with acute appendicitis at DR. M. Djamil Padang in 2017 – 2019 with 112 samples using total sampling technique. The research data were analyzed using the univariate test and presented in the form of frequency and percentage distribution tables. Results: Characteristics of acute appendicitis patients at RSUP DR. M. Djamil Padang, based on age, acute appendicitis mostly occurred in the late adolescent age group (17 – 25 years). Characteristics based on sex, acute appendicitis mostly occured in males – 64 people (57.1%). Characteristics based on modified Alvarado score at most with a score of 9 (Definite acute appendicitis) – 62 people (55.4%). The most characteristics based on the management of acute appendicitis was open appendectomy – 97 people (86.6%). Conclusion: The result of this study show that acute appendicitis in late adolescents with an age range of 17 – 25 years. Acute appendicitis mostly in males with the most modified Alvarado score with 9 scores and open appendectomy was the main choice.